Personality in sentenced for crimes of sexual assault against children and adolescents - Tuya Espinoza, Gabriela Isabel (2022)
Objective. To identify and analyze the clinical characteristics of personality in persons sentenced for crimes of sexual assault against children and adolescents. Methods. A non-experimental, descriptive, cross-sectional study was conducted with 157 male inmates in the Miguel Castro Castro penitentiary, Lima, Peru. A sociodemographic form and the Millon Multiaxial Clinical Inventory II (MCMI-II) were used to determine clinical personality diagnoses. Results. At the time of the study, the sentenced persons had sentences ranging from 12 years to life imprisonment (N = 24.8; SD = 9.58), were aged between 19 and 66 years (M = 38.6; SD = 10.69) and most of them had completed high school (43.3%). The clinical personality diagnoses in moderate and high levels of those sentenced for the crime of rape against children were compulsive, dependent, narcissistic, histrionic, paranoid, drug dependence and delusional overflow. Conclusion. The majority presented two or more rigid, maladaptive and inflexible clinical personality scales, such findings may be useful in therapeutic and treatment programs for child sex offenders.